2021
DOI: 10.1021/acsearthspacechem.1c00056
|View full text |Cite
|
Sign up to set email alerts
|

Simulation of Monoterpene SOA Formation by Multiphase Reactions Using Explicit Mechanisms

Abstract: The formation of terpene secondary organic aerosol (SOA) was simulated using the unified partitioning aerosol phase reaction model that predicted multiphase reactions of hydrocarbons in the presence of electrolytic inorganic aerosols. To predict oxygenated products from the atmospheric oxidation of terpenes, the master chemistry mechanism, an explicit gas kinetic mechanism, was implemented. The resulting products were then classified into 51 lumping groups using mass-based stoichiometric coefficients according… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

2
4

Authors

Journals

citations
Cited by 24 publications
(37 citation statements)
references
References 99 publications
5
32
0
Order By: Relevance
“…In this study, the SRH values of the chamber-generated SOA (oxidized from β-pinene, toluene, and 1,3,5-trimethylbenzene), which were internally mixed with the ammonium sulfate system ( f anion = 0.5–0.8), were simulated against observations based on microscopic data. The SOA model parameters comprising MW, O/C ratios, and H bond were estimated using the aerosol composition predicted using the UNIPAR SOA model. ,,, The detailed description of organic parameters is shown in Section S3 and Table S4 in the Supporting Information. For all SOA data, LLPS was observed when RH was less than 90%.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In this study, the SRH values of the chamber-generated SOA (oxidized from β-pinene, toluene, and 1,3,5-trimethylbenzene), which were internally mixed with the ammonium sulfate system ( f anion = 0.5–0.8), were simulated against observations based on microscopic data. The SOA model parameters comprising MW, O/C ratios, and H bond were estimated using the aerosol composition predicted using the UNIPAR SOA model. ,,, The detailed description of organic parameters is shown in Section S3 and Table S4 in the Supporting Information. For all SOA data, LLPS was observed when RH was less than 90%.…”
Section: Resultsmentioning
confidence: 99%
“…The prediction of ERH can significantly improve the accuracy of the SOA model due to the pathway of SOA formation via the aqueous reactions of organic species. For example, chamber studies showed that SOA formation considerably decreases at ERH when RH decreases during daytime. ,, Owing to the mitigation of SO 2 emissions in recent years (reduced more than 74% from 2010 to 2020; ), sulfate in ambient aerosols has been gradually reduced. However, a high fraction of ammonium nitrate can appear in an ambient aerosol under the low sulfate .…”
Section: Atmospheric Implications and Uncertaintiesmentioning
confidence: 99%
See 1 more Smart Citation
“…The configuration of the UNIPAR model for SOA formation from each precursor has been described in prior studies (Beardsley and Jang, 2016;Im et al, 2014;Cao and Jang, 2010;Zhou et al, 2019;Yu et al, 2021b;Han and Jang, 2021). The predetermined mathematical equations and the model parameters employed in the UNIPAR model have been evaluated in the UF-APHOR chamber for various aromatic volatile organic compounds (VOCs) and biogenic VOCs (terpenes and isoprene) under varying aqueous salted seeds, NOx, SO2, humidity levels, and temperatures.…”
Section: Unipar Soa Modelmentioning
confidence: 99%
“…The conventional SOA module in regional models has no feature for SOA formation via aqueous phase reactions of different oxygenated products formed from various HCs. Our laboratory's recent research efforts (Beardsley and Jang, 2016;Im et al, 2014;Cao and Jang, 2010;Zhou et al, 2019;Yu et al, 2021b;Han and Jang, 2021) have improved the state of the art science by developing the UNIfied Partitioning-Aerosol phase Reaction (UNIPAR) model, which utilizes explicit gas chemistry to predict SOA mass based on multiphase reactions. In the UNIPAR model, the products predicted using explicit gas mechanisms are lumped based on volatility and emerging chemistry in the aerosol phase.…”
Section: Introductionmentioning
confidence: 99%